2018
DOI: 10.1186/s12911-018-0654-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MetaMap and cTAKES for entity extraction in clinical notes

Abstract: BackgroundClinical notes such as discharge summaries have a semi- or unstructured format. These documents contain information about diseases, treatments, drugs, etc. Extracting meaningful information from them becomes challenging due to their narrative format. In this context, we aimed to compare the automatic extraction capacity of medical entities using two tools: MetaMap and cTAKES.MethodsWe worked with i2b2 (Informatics for Integrating Biology to the Bedside) Obesity Challenge data. Two experiments were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 15 publications
0
45
0
1
Order By: Relevance
“…This heterogeneity of expressions poses challenges for efforts to use natural language processing algorithms to convert free text neurological examinations into UMLS concepts [7,8]. In a pilot study with NLM MetaMap [38,39] in the batch mode, we were able to convert 70.3% of the 2286 test phrases to UMLS concepts. A higher conversion yield might be possible with additional post-processing and pre-processing of the longer and more complex test phrases.…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity of expressions poses challenges for efforts to use natural language processing algorithms to convert free text neurological examinations into UMLS concepts [7,8]. In a pilot study with NLM MetaMap [38,39] in the batch mode, we were able to convert 70.3% of the 2286 test phrases to UMLS concepts. A higher conversion yield might be possible with additional post-processing and pre-processing of the longer and more complex test phrases.…”
Section: Discussionmentioning
confidence: 99%
“…Existing tools, such as MetaMap and cTAKES, provide programmatic means for mapping text to concepts in the UMLS. 29 However, UMLS was designed for written text, not for spoken medical conversations. The differences in (1) spoken vs. written language and (2) lay vs. expert terminology, cause inaccuracies and word mismatching when using existing tools for medical language processing from medical conversations.…”
Section: Challenge 3: Information Extraction In Clinical Conversationsmentioning
confidence: 99%
“…With MetaMap's default settings, the phrase "I am feeling fine" would result in "I" mapped to "blood group antibody I", "feeling" mapped to "emotions", and "fine" mapped to "qualitative concept" or "legal fine". Therefore, additional steps must be taken to identify semantic types and groups to control the way text is mapped to medical concepts 29 or develop rules to filter irrelevant terms, which depending on the text can be a timeconsuming trial and error process.…”
Section: Challenge 3: Information Extraction In Clinical Conversationsmentioning
confidence: 99%
“…For example, Hassanzadeh et al evaluated the NER tools used by the studies in Table 1 and found that the F1-score ranged from 5% to 75% for different types of UMLS concepts [24]. Likewise, Reátegui et al found that the F1-score of the NER tools varied from 44% to 96% for different types of diseases [26]. Importantly, errors produced in the NER step may diminish the effectiveness of bio-concept embeddings.…”
Section: Introductionmentioning
confidence: 99%